Impact of influencer marketing on consumers’ purchase intention - Yeo, Xin Yi (2023)
This study aims to examine the impact of influencer marketing on consumers' purchase intention in the context of food and beverage industry. Drawing upon the theoretical frameworks of the Theory of Reasoned Action (TRA) and Theory of Planned Behaviour (TPB), the study investigates the influence of independent variables, including influencer type (IV1), brand familiarity (IV2), sponsorship disclosure (IV3), influencer's expertise (IV4), and trustworthiness(IV5), on consumers' purchase intention (DV) as the dependent variable. A quantitative research approach was used, and data were obtained from a sample of 230 respondents using an online questionnaire. The findings confirm H1 by indicating that microcelebrities have a beneficial impact on consumers' purchase intentions when compared to traditional celebrities. The study, however, discovered no significant association between brand familiarity and consumers' purchase intention, resulting in the rejection of H2. Sponsorship disclosure and influencer expertise, on the other hand, were found to have a positive association with consumers' purchase intention, supporting H3 and H4, respectively. Surprisingly, the study discovered that trustworthiness had no effect on consumers' purchasing intentions, hence rejecting H5. These findings add to our understanding of the efficacy of influencer marketing in food and beverage industry and have practical consequences for marketers and advertisers. The study also cites many limitations, such as time constraints and a regional focus, which provide possibilities for future research to further investigate the dynamics of influencer marketing and its impact on consumer behaviour.